SYSTEMATIC LITERAUR REVIEW: MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MUATAN PELAJARAN IPS DI SEKOLAH DASAR - Didi Faris Susanto; Aramudin, Aramudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The importance of innovating to support social studies learning at the elementary school level is very crucial. One form of innovation that can be implemented is through the development of learning media. The use of learning media aims to arouse students' enthusiasm and motivation to learn, which in the end can improve their learning outcomes. This research aims to review literature related to the use of Augmented Reality (AR) media in social studies learning in elementary schools. The research method used is Systematic Literature Review (SLR). Data was collected by documenting and reviewing all articles related to AR published in the 2018-2024 period. A total of 8 accredited national and international journal articles obtained from the Google Scholar database were used in this research. The research results show that AR media can improve learning outcomes, learning motivation, creative thinking abilities, and understanding of concepts in Social Sciences (IPS) learning.